1994
DOI: 10.1264/microbes1986.9.55
|View full text |Cite
|
Sign up to set email alerts
|

Use of Polymerase Chain Reaction-amplified 16S rRNA Gene Sequences to Identify Pink-pigmented Bacteria Found in a Potable Water Treatment System.

Abstract: Two strains of pink-pigmented, chlorine-resistant bacteria, GK101 and GK118, previously isolated from pink-colored microbial biomass occurring in a potable water treatment system were studied phylogenetically by using 16S rRNA gene sequence information. 16S ribosomal DNA (rDNA) fragments of approximately 1.5 kbp were amplified by the polymerase chain reaction (PCR) from crude cell lysates of the isolates and sequenced directly by a combined method consisting of linear PCR sequencing and automated fluorescence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Figure 3 contains two neighborjoining trees showing the phylogenetic positions of bacterial isolates F and G. Isolate F formed a cluster with Methylobacterium sp. strain GK 101 (14), supported by a bootstrap value of 899. Isolate G formed a cluster with P. azotoformans, P. synxantha, and P. mucidolens, supported by a bootstrap value of 989.…”
mentioning
confidence: 90%
“…Figure 3 contains two neighborjoining trees showing the phylogenetic positions of bacterial isolates F and G. Isolate F formed a cluster with Methylobacterium sp. strain GK 101 (14), supported by a bootstrap value of 899. Isolate G formed a cluster with P. azotoformans, P. synxantha, and P. mucidolens, supported by a bootstrap value of 989.…”
mentioning
confidence: 90%
“…They are phenotypically and chemotaxonomically quite similar, and phenotypic differences among the species are found in only limited properties, such as carbon source utilization. In recent years, 16S rRNA sequence information has been used for phylogenetic placement and identification of different physiological groups of methylotrophic proteobacteria, including Methylobacterium species (4,6,27,51,52). The molecular data have shown that the genus Methylobacterium represents a line of descent in the alpha-2 subclass of the class Proteobacteria.…”
mentioning
confidence: 99%
“…Our approaches to this investigation were twofold: one involved physiological and biochemical characterization of the isolates, followed by numerical analysis of phenotypic profiles, and the other involved genetic analysis by PCR sequencing of 16S ribosomal DNA (rDNA). A previous phylogenetic study has shown that some Methylobacterium species, including those closely related to M. extorquens, are responsible for the formation of pink biofilms in a potable water treatment system (27).…”
mentioning
confidence: 99%
“…[32] Of principal relevance to the present research, however, is the fact that Methylobacterium spp. have been isolated from soils.…”
Section: Methylobacteriummentioning
confidence: 86%